The effectiveness of fraud prevention and detection techniques in Malaysia : perception of bankers in Islamic Banks / Irda Syahira Khair Anwar - Khair Anwar, Irda Syahira (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2012)
Bank fraud may represent one of the major causes of bankruptcy in the world. Motivated by previous bank fraud cases in India (The Ketan Parekh fraud) and in Dubai (Dubai Islamic Bank scandal), this research aims to focus on fraud in Malaysia's Islamic banks. This research is carried out to identify the common types of bank fraud that frequently incurred in Islamic banks, the underlying determinants and the amount of losses as a result of fraud cases. Also, this study aims to provide an insight on the perception of bankers towards the effectiveness of fraud prevention and detection techniques in Malaysian Islamic banks. In addition, this study aims to contribute an empirical analysis on the comparison between demographic variables such as gender, education level and working experience in banking industry towards perception on the effectiveness of fraud prevention and detection techniques. The respondents are among managers and officers within Islamic banks in Malaysia. Out of total the 255 questionnaires sent to the respondents, 146 responses were received, giving a response rate of 57.25%. The findings indicated fraudulent statement is the most common fraud in Islamic banks followed by credit card fraud. The major determinants of fraud in Islamic banks are greed (18%) and non compliance (17%). Meanwhile, the losses incurred due to fraud by these banks approximately more than RM1 million. In fact, bank reconciliation, password protection as well as internal control review and improvement represents as the top three most effective techniques for combating fraud in Islamic banks. Moreover, the results shov/ed that there are no significant differences between gender, education level and working experience of a banker towards their perception on the effectiveness of fraud prevention and detection techniques. This study could benefit both academicians and practitioners in term of evaluation of the current level of protection against bank fraud in Malaysia. This study also could contribute for improvement in fraud prevention and detection techniques by participating banks.